OFR-28-72 Systems Analysis Of An Inherently Explosion-Proof Coal Mining Operation (The National Institute for Occupational Safety and Health (NIOSH), 2012)
The inherently explosion-proof mine (EPM) concept is based upon the non-flammability of certain combustible-oxidant-inert gas mixtures, and the effect of partial pressure of gases on physiological reactions. In a properly controlled underground environment, gas explosions are impossible, men can do work, and relatively high concentrations of methane would be permitted. A systems analysis has been performed to examine the physiological, engineering, and economic feasibility of such a concept, and methods and equipment are recommended for maintaining an EPM atmosphere in a bituminous coal mine producing a nominal two million tons of clean coal per year. It is concluded that: engineering feasibility can be demonstrated using subsystems and components that can be designed and built within the present state-of-the-art, that economic feasibility is possible within approximately five years, and that physiological feasibility is sufficiently promising to warrant continued investigation.